Overview of selected completed prospective studies on PSMA-targeted radioligand therapy with [177Lu]Lu-PSMA-617 in metastatic castration-resistant prostate cancer - Karimzadeh, Amir; Lehnert, Wencke; Koehler, Daniel; Shenas, Farzad; Kisters, Anna; Apostolova, Ivayla; Klutmann, Susanne; Adam, Gerhard; Sauer, Markus (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Theranostics in nuclear oncology combines diagnostic and therapeutic procedures using radiotracers to target tumor cells. Prostate-specific membrane antigen (PSMA) is a key target in metastatic prostate cancer, and the radioligand [177Lu]Lu-PSMA-617, which binds to PSMA, has shown promising results in treating metastatic castration-resistant prostate cancer (mCRPC), leading to its approval by the European Medicines Agency in 2022.In this narrative review, the current evidence of [177Lu]Lu-PSMA-617 in mCRPC was discussed in the context of selected studies and the joint EANM/SNMMI guidelines for Lutetium-177-labeled PSMA-targeted radioligand therapy.The use of [177Lu]Lu-PSMA-617 for post-chemotherapy mCRPC is supported by substantial evidence from the phase II TheraP and the phase III VISION trials, demonstrating its safety and efficacy. The theranostic approach identifies patients likely to benefit from [177Lu]Lu-PSMA-617, which is effective only in tumors with sufficient PSMA expression, as detected by PSMA-ligand PET/CT, which is also used for response assessment.The success of [177Lu]Lu-PSMA-617 in post-chemotherapy mCRPC patients has led to further ongoing studies evaluating its use earlier in the treatment sequence, prior to chemotherapy. To ensure beneficial treatment outcome, adequate patient selection and evaluation of imaging-based response through PSMA-ligand PET/CT is necessary.
Keywords: prostate-specific membrane antigen (PSMA); radioligand therapy (RLT); metastatic castration-resistant prostate cancer (mCRPC); [177Lu]Lu-PSMA-617